Literature Study: Decreased Productivity in Adolescents Due to Undernutrition - Dimas Rizky Eddeliyanto Widodo; Brigitte Sarah Renyoet (Universitas Ibn Khaldun Bogor, 2023)
Malnutrition is a nutritional deficiency, and lack of nutritional intake due to low consumption of energy and protein in food so it does not meet nutritional intake needs. Problems that can arise from malnutrition are stunting, wasting, and underweight. The purpose of this study was to determine the relationship between adolescent productivity and malnutrition. The method used in this research is a literature review using databases in PubMed/NCBI, Google Scholar, ScienceDirect, ResearchGate, and BMC Research Notes, with keywords using English and Indonesian. Five journals were obtained with details of two international journals and three national journals, which discussed malnutrition in adolescents which affected productivity in the academic, physical, mental, nutritional intake, and social environment. The nutritional status of adolescents can be influenced by several factors, one of which is diet. Erratic eating patterns can lead to undernutrition which results in a lack of nutrition knowledge. The importance of following health education and nutrition education to increase knowledge about balanced nutrition.